Correlation among Blood Sugar Levels, C-Reactive Protein, Total Lymphocyte Count with SOFA Score on Sepsis COVID-19 Patients - Fajari, Nanang Miftah; Hartono, Ivan; Rudiansyah, Mohammad; Agung SNC, Wiwit; Yasmina, Alfi (Universitas Brawijaya, 2024)
Background: COVID-19 is a caused a pandemic since early January 2020. Sequential Organ Failure Assessment (SOFA) score can assess organ dysfunction in the state of Sepsis MODS. Aim: This study aims to determine the relationship between Blood Sugar Levels, C-Reactive Protein (CRP), and Total Lymphocyte Count (TLC) with SOFA score in COVID-19 patients with Sepsis. Methods: An observational study using the cross-sectional method was carried out in 2020-2021 at Ulin Hospital Banjarmasin with a total sample of 87 participants. Results: Based on the Spearman test, there were a positive correlation between Random Blood Sugar levels and SOFA with the scores r = 0.778 (p = 0.000); significant negative correlation between TLC and SOFA with the score r = -0.409 (p = 0.000); and no significant correlation between CRP and SOFA with the score r = -0.077 (p = 0.507). The multivariate test showed that the correlation value for each Random Blood Sugar with a SOFA score is R=0.664 (p=0.000), and the Total Lymphocyte Count with a SOFA score is R=-0.270 (p=0.001). The statistical analysis model revealed that Blood Sugar Levels and Total Lymphocyte Count could predict SOFA scores of as much as 60.9%. Conclusion: Blood sugar levels can be a marker of poor prognosis in COVID-19 patients with Sepsis. Hyperglycemia can be caused by pancreatic cell damage due to SARS-CoV2 invasion, acute insulin resistance, and inflammation caused by Sepsis and COVID-19. Total Lymphocyte Count is one of the many factors contributing to organ dysfunction caused by Sepsis in COVID-19. Keywords: COVID-19, Sepsis, SOFA Score, Prognosis